The Role of Entrepreneurial Marketing and Entrepreneurial Orientation in Improving SMEs Performance (Study on Kampung Tahu Kediri) - Ambarwati, Diana; Munawaroh, Nuril Aulia; Ramadhan, Tri Sugiarti; Rahmadi, Afif Nur (Ekonika : Jurnal Ekonomi Universitas Kadiri, 2025)
This study aims to analyze the influence of entrepreneurial marketing and entrepreneurial orientation on the performance of small and medium-sized tofu producers in Kampung Tahu Kediri, considering the role of marketing strategy as a mediator and marketing capability as a moderator. The research population consisted of all SMEs that are members of the Paguyuban Tahu in Kampung Tahu Kediri, with a sample size of 43 respondents selected using saturated sampling. The PLS-SEM approach was used to evaluate primary data collected via surveys. The results indicate that entrepreneurial marketing has a positive and significant effect on marketing strategy and SME performance, while entrepreneurial orientation does not have a significant effect and tends to be negative on both; marketing strategy contributes positively and significantly to SME performance, but marketing capability does not have a significant effect or moderation in the relationship, and marketing strategy does not mediate the influence of entrepreneurial marketing and entrepreneurial orientation on SME performance. The novelty of this study lies in the strong direct impact of entrepreneurial marketing on the performance of tofu-processing SMEs in a local community context, while entrepreneurial orientation shows a negative tendency, providing new insights into the dynamics of entrepreneurial characteristics in traditional businesses. The implications of these findings emphasize the importance of focusing on product innovation and adaptive marketing strategies, as well as the need for government and supporting institutions to strengthen marketing capabilities and business sustainability of SMEs